Asbestos danger in central Europe is not yet over - the situation in the Czech Republic - Urban, Miroslav; Pelclová, Daniela; Urban, Pavel; Vít, Michael; Urban, Peter; Fenclová, Zdenka (Central European journal of public health, 2022)
OBJECTIVES: In the Czech Republic, asbestos has been classified as a known human carcinogen since 1984. The use of asbestos-containing products was limited to scenarios where the use of other materials was not possible. Since 1997, the manufacture of asbestos materials has been forbidden, and in 1999, the import, manufacture and distribution of all types of asbestos fibres was legally banned by Act No. 157/1998 Coll. Although the use of asbestos is forbidden, the risk of exposure still exists given the ongoing demolition and reconstruction of buildings in which asbestos has been used. In addition, a novel risk has arisen through the quarrying of asbestos-containing aggregates and their subsequent use. The aim of this paper was to describe and evaluate asbestos in terms of history, legislation, current risk of occupational exposure and its health consequences in the Czech Republic over the last three decades. METHODS: This retrospective descriptive study used the collected data on occupational exposure and occupational diseases. The counts of workers occupationally exposed to asbestos were obtained from the Registry of Work Categorization; the numbers and structure of occupational diseases caused by asbestos were taken from the Czech National Registry of Occupational Diseases. Data on the total number of mesothelioma cases recorded in the Czech National Cancer Registry was provided by the Institute of Health Information and Statistics of the Czech Republic. RESULTS: A total of 13,112 subjects were registered as occupationally exposed to asbestos during the period 2001-2020. A total of 687 cases of asbestos-related occupational diseases were reported in the period 1991-2020 in the Czech Republic, comprising 178 cases of asbestosis, 250 cases of pleural hyalinosis, 168 cases of pleural or peritoneal mesothelioma, 90 cases of lung cancer, and one case of laryngeal cancer. The data from the Czech National Cancer Registry, available for a shorter period (1991-2018), reveal 1,389 cases of mesothelioma, of which only ~11% were recognised as occupational, despite the fact that the occupational causality of mesotheliomas is estimated to be up to 90% of mesotheliomas. Moreover, the latency of mesotheliomas since the last occupational exposure reached up to 50 years and this trend is still slightly increasing, unlike asbestosis, where a high cumulative dose of inhaled asbestos is needed. The real proportion of occupational lung cancers may obviously be even higher, especially in smokers, where occupational causes including asbestos are not suspected by most physicians. CONCLUSION: Czech data on asbestos-related occupational diseases, especially cancers, are grossly underestimated, which is most apparent through the low proportion of mesotheliomas diagnosed as occupational. Asbestos materials in older buildings remained in situ and may represent a danger during reconstruction works. The current source of exposure appears to be quarrying of asbestos-containing aggregate and its subsequent use. Awareness of the professional community is therefore crucial, not only for the possibility of compensating those affected, but also for the early detection of the diseases through the dispensary of exposed persons.
Keywords: Occupational Exposure; nádory plic; Lung Neoplasms; unrecognised occupational diseases; Humans; Occupational Diseases; asbestos; nemoci z povolání; lidé; Asbestos; asbestos ban; Asbestosis; azbestóza; Retrospective Studies; pracovní expozice; Mesothelioma; mezoteliom; Czech Republic; retrospektivní studie; work categorization; azbest; Česká republika; asbestos-related diseases